2002
DOI: 10.1016/s0092-8674(02)00873-5
|View full text |Cite
|
Sign up to set email alerts
|

Modular Recognition of RNA by a Human Pumilio-Homology Domain

Abstract: Puf proteins are developmental regulators that control mRNA stability and translation by binding sequences in the 3' untranslated regions of their target mRNAs. We have determined the structure of the RNA binding domain of the human Puf protein, Pumilio1, bound to a high-affinity RNA ligand. The RNA binds the concave surface of the molecule, where each of the protein's eight repeats makes contacts with a different RNA base via three amino acid side chains at conserved positions. We have mutated these three sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
705
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(724 citation statements)
references
References 31 publications
15
705
3
1
Order By: Relevance
“…The binding and translational repression requires the interaction of Puf6 protein with the consensus UUGU segments, known to be recognized by PUF family proteins (Wang et al 2002), in the 3ЈUTR of the ASH1 mRNA. Deletion of puf6 or mutation of the UUGU elements of the mRNA increased the intracellular Ash1p concentration and significantly affected asymmetric Ash1p segregation, evidently due to the disruption of the interaction between Puf6p and its target mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding and translational repression requires the interaction of Puf6 protein with the consensus UUGU segments, known to be recognized by PUF family proteins (Wang et al 2002), in the 3ЈUTR of the ASH1 mRNA. Deletion of puf6 or mutation of the UUGU elements of the mRNA increased the intracellular Ash1p concentration and significantly affected asymmetric Ash1p segregation, evidently due to the disruption of the interaction between Puf6p and its target mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the NLS suggested that Puf6p may be a nuclear protein. PUF proteins have been identified to function through interaction with the 3ЈUTRs of Drosophila hb mRNA, C. elegans fem-3 mRNA, and yeast HO mRNA (Wharton and Struhl 1991;Murata and Wharton 1995;Zhang et al 1997;Wharton et al 1998;Tadauchi et al 2001;Wang et al 2002). Although these 3ЈUTRs share little overall similarity to each other, they all contain the UUGU tetranucleotide, the conserved segment important for PUF protein function.…”
Section: Ash1 Mrna Contains Conserved Puf Recognition Sequences In Thmentioning
confidence: 99%
“…A recent and striking specific example (Fig. 3) comes from the Puf proteins or pumilio homology domains, which are a repeated a-helical structure in which each helical repeat supplies an amino acid side chain to stack on and sandwich successive bound RNA bases (Wang et al 2002). Thus by either of the above two means, an aromatic amino acid side chain may also be a group that strongly localizes an amino acid so that its adjacent profile may be determined.…”
Section: The Polar Profilementioning
confidence: 99%
“…This description should not be thought of as exhaustive; for example, SAM I and SAM III use a syn Fig. 3 Stereo pair of nucleobase-amino acid stacking within the human pumiliohomology domain bound to RNA (Wang et al 2002). The magenta projections from the arc of a-helical repeats on the right are stacked amino acid side chains from position 13 of each pumilio-homology domain repeat.…”
Section: The Polar Profilementioning
confidence: 99%
“…Stacking interactions involving tyrosine or phenylalanine are more common. The Tis11d ZnFs, which recognize AU-rich elements (24), and the pumilio repeat proteins, which bind elements in the 3Ј untranslated regions of target mRNAs (25), both display such stacks.…”
Section: The Binding Preferences Of Zranb2 Corroborate Functional Splmentioning
confidence: 99%